2018
DOI: 10.1016/j.ijpharm.2018.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary administration of a dry powder formulation of the antifibrotic drug tilorone reduces silica-induced lung fibrosis in mice

Abstract: The aim of this work was to study the antifibrotic effect of pulmonary administration of tilorone to lung fibrosis. L-leucine coated tilorone particles were prepared and their aerosolization properties were analyzed using two dry powder inhalers (Easyhaler and Twister). In addition, the biological activity and cell monolayer permeation was tested. The antifibrotic effect of tilorone delivered by oropharyngeal aspiration was studied in vivo using a silica-induced model of pulmonary fibrosis in mice in a prevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Vartiainen et al used aspiration to administer silicon dioxide to induce pulmonary fibrosis, after which they used aspiration to deliver tilorone as a therapy to treat fibrosis. The authors observed a significant reduction in the histological fibrosis score with the aspiration delivery method [ 34 ]. Further, Chakravarthy et al have used the aspiration technique to deliver formulations to the lungs and target the alveolar macrophages [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vartiainen et al used aspiration to administer silicon dioxide to induce pulmonary fibrosis, after which they used aspiration to deliver tilorone as a therapy to treat fibrosis. The authors observed a significant reduction in the histological fibrosis score with the aspiration delivery method [ 34 ]. Further, Chakravarthy et al have used the aspiration technique to deliver formulations to the lungs and target the alveolar macrophages [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nanoparticles offer new possibilities for improving drug release properties and obtaining optimal results in the treatment of inflammatory lung diseases by modifying the physical properties of the inhaled drug delivery carriers, such as particle size, shape, density, surface charge and other surface modifications [ 79 , 80 ]. Vartiainen et al [ 81 ] fabricated a dry powder nanoparticle formulation that contained 29.4% of tilorone, 9.6% of leucine and 61.0% of mannitol for silica-induced PF treatment. The formulation promoted more stable penetration through the monolayer of lung cells.…”
Section: Nanoparticlesmentioning
confidence: 99%
“…There have been some clinical applications to treat IPF by PDDS in western medicine. For example, Rasool [ 134 ] prepared an ultrasonic nebulizer of pirfenidone, and Vartiainena with l -leucine coated tilorone dry particles [ 135 ], which all provide the basis for the treatment of IPF.…”
Section: Pulmonary Drug Delivery System For Tcm To Treat Ipfmentioning
confidence: 99%